Significance of exosomes in osteosarcoma research: a systematic review and meta-analysis of a singular clinical investigation - Liu, Xuehong; Ye, Jingyao; Guo, Wenlong; Wang, Junqing (Frontiers in Cell and Developmental Biology, 2024)
BackgroundOsteosarcoma is the most prevalent among primary bone malignancies, and its standard intervention involves neoadjuvant chemotherapy - surgical adjuvant chemotherapy (MAP regimen) with adriamycin, cisplatin, and high-dose methotrexate. Early-stage osteosarcoma can be effectively treated with surgical resection along with chemotherapy or radiotherapy. However, as the cancer progresses, the efficacy of chemo- and radiotherapy decreases, and the associated problems increase. The current understanding of osteosarcoma development, diagnosis, and treatment does not meet clinical demands. More recently, there has been a significant increase in exosome-associated osteosarcoma research, potentially opening up novel possibilities for osteosarcoma research.PurposeWe comprehensively evaluated and analyzed the advancement of preclinical research related to exosome-osteosarcoma. We aimed to establish a practical, theoretical foundation for future research initiatives.Study designThe selected design was a systematic review and meta-analysis.MethodsScientific databases, such as PubMed, Embase, The Cochrane Library, and Web of Science, were extensively screened for exosome and osteosarcoma articles. Two highly trained investigators separately reviewed the literature, extracted relevant information, and assessed study quality. Subsequently, we conducted a meta-analysis using Review Manager 5.4.ResultsIn total, 25 animal-based randomized controlled trials (RCTs) were selected for analysis. Among them, 13 studies provided strong evidence of cellular exosomes regulating osteosarcoma development from bone marrow mesenchymal stem cells, osteosarcoma cells, and macrophages. In addition, 12 studies demonstrated the therapeutic potential of exosomes in managing osteosarcoma, among which 7 studies transplanted transfected exosomes directly into animals as drugs, and five studies employed exosomes as drug carriers, which were next transplanted into animals.ConclusionBased on our meta-analysis, macrophages strongly modulate osteosarcoma development, and engineered exosomes provide the most effective exosome-based osteosarcoma treatment.